Through evangelizing eyes: American missionaries to Oman - al-Hajri, Hilal (Proceedings of the Seminar for Arabian Studies, 2011)
This paper is concerned with American missionaries, who were in Oman from 1893 to 1976. Their initial aim was the conversion of the Arabs of Oman from Islam to Christianity. Their main tools were evangelism, education, and medical service. They travelled widely and left a number of books and travel accounts about the country. The primary aim of this paper is to investigate their discourse on Oman within the framework of orientalism. This study argues that American missionary writings on Oman are diverse and ambivalent. They consist of different attitudes towards Omani culture and people. While some of the missionaries were products of general Western orientalism, in terms of cultural imperialism and treating 'the other' as inferior, some of them were individually impartial.